Phthalazinone Inhibitors of Inosine-5′-Monophosphate Dehydrogenase from Cryptosporidium parvum - Johnson, Corey R. (2012)
Cryptosporidium parvum (Cp) is a potential biowarfare agent and major cause of diarrhea and malnutrition. This protozoan parasite relies on inosine 5′-monophosphate dehydrogenase (IMPDH) for the production of guanine nucleotides. A CpIMPDH-selective N-aryl-3,4-dihydro-3-methyl-4-oxo-1-phthalazineacetamide inhibitor was previously identified in a high throughput screening campaign. Herein we report a structure-activity relationship study for the phthalazinone-based series that resulted in the discovery of benzofuranamide analogs that exhibit low nanomolar inhibition of CpIMPDH. In addition, the antiparasitic activity of select analogs in a Toxoplasma gondii model of C. parvum infection is also presented.